Our dwelling place: the making of a sense of place in semi-rural England - Saegusa, Kentaro (The University of Edinburgh, 2004)
This thesis focuses on a place making process in semi-rural England. 'Place' in this thesis means personally meaningful environment. The thesis describes and analyses various efforts made by residents in two parishes in West Midlands to connect themselves with their immediate environment. Most of the agents appear in this thesis are in-migrants of various lengths of residency. Unlike those who were born and bred there, those who moved in later in their lives cannot claim the 'natural' relationship to the environment. Their relationship to the environment is not given by birth. They have to build up the relationship consciously. The thesis examines what elements are mobilised in the process and how.

The general ethnographic details of two sites are given in Part I. Part I also plays the role of the introductory section to the discussion to be developed in Part II. The highlighted points are different in two sites. In Dymock part, a history of the parish and people's activities generated around the history are described in detail. In Colwall part, on the other hand, a planning issue and a debate caused by a proposed housing development are followed in detail.

Part II is organised by a theme rather than a location. The first chapter in this part is dedicated to the issue of history and memory. How the elements of time and past is deployed in the process of place making is examined. More specifically, the chapter focuses on the passion for recording the history in the forms of document and performance. The second chapter examines a regulatory framework of space, or the space management system, in England and the way people negotiate with the system to form or maintain the ideal place. The chapter also considers a class element involved with the process. Throughout Part II, the desire of control and the sense of ownership are considered.

People in both Dymock and Colwall often mention that they live in the countryside, which has a special meaning for them. Living in the countryside forms the crucial part of their sense of place. In the final part, the thesis examines this heavily culturally value-laden space of English countryside. Part III describes the recent debate over the fox-hunting with dogs which reveals various sentiments that are not always accessible or acceptable for those who are described in previous Parts. This Part also examines the idea of stewardship of the countryside as a compromise to create a sense of shared ownership of the place.